Friends, Gifts, and Cliques: Social Proximity and Recognition in Peer-Based Tournament Rituals - Aadland, Erik; Cattani, Gino; Ferriani, Simone (Academy of Management Journal, 2019)
Two main accounts of the effect of social proximity between candidates competing for recognition and members of the evaluating audience can be extrapolated from extant literature on peer-based tournament rituals and cultural fields. Following a Bourdieusian tradition, one account—which we label “self-reproduction”—points to the catalyzing effect of social proximity in shaping recognition along relational lines. Drawing from recent scholarship on social evaluation, a second account—which we call “intellectual distance”—suggests that social proximity deters recognition. We probe the influence of different articulations of social proximity (i.e., direct ties, cliquishness, and reciprocity) on recognition by studying awarding decisions within the context of the Norwegian advertising industry. Interviews with key informants as well as econometric results suggest that, while self-reproduction tends to prevail over intellectual distance, these effects coexist and their relative influence varies across levels of recognition. We gauge the relative saliency of the two accounts by using a mixed methods approach. Important implications for research on social evaluation and recognition in peer-based tournament rituals are drawn.